The use of sodium hexametaphosphate in the extraction of guava juice for jelly-making - Bautista, Emma S. (1959)
The effect of adding sodium hexametaphosphate during the extraction of guava juice on the relative viscosity, pH, pectin content, and the quality of the jellies made from the juice is determined. A polyphosphate-treated batch and a control batch were prepared for purposes of comparison. The effect of pasteurization and storage for a period of one month on the above properties were also determined.